2011
DOI: 10.1016/j.cellsig.2011.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear localization of pyruvate dehydrogenase complex-E2 (PDC-E2), a mitochondrial enzyme, and its role in signal transducer and activator of transcription 5 (STAT5)-dependent gene transcription

Abstract: STAT (signal transducer and activator of transcription) proteins play a critical role in cellular response to a wide variety of cytokines and growth factors by regulating specific nuclear genes. STAT-dependent gene transcription can be finely tuned through the association with cofactors in the nucleus. We showed previously that STAT5 (including 5a and 5b) specifically interacts with a mitochondrial enzyme PDC-E2 (E2 subunit of pyruvate dehydrogenase complex) in both leukemic T cells and cytokine-stimulated cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 53 publications
(78 reference statements)
6
40
0
Order By: Relevance
“…The nuclear complex of PDC, PKM2, and p300, as discussed earlier, acetylates a specific histone, resulting in the activation of the transcription of a specific gene (arylhydrocarbon receptor) [6] (Figure 2). Similarly, the PDCE2 subunit has been found to form complexes with the transcription factor STAT5 [73]. These data support the existence of mechanisms that regulate localized acetylation in the nucleus by the strategic delivery of an ACPE in sub-nuclear domains.…”
Section: Acetyl-coa-producing Enzymes (Acpes) and Histone Acetylationsupporting
confidence: 61%
“…The nuclear complex of PDC, PKM2, and p300, as discussed earlier, acetylates a specific histone, resulting in the activation of the transcription of a specific gene (arylhydrocarbon receptor) [6] (Figure 2). Similarly, the PDCE2 subunit has been found to form complexes with the transcription factor STAT5 [73]. These data support the existence of mechanisms that regulate localized acetylation in the nucleus by the strategic delivery of an ACPE in sub-nuclear domains.…”
Section: Acetyl-coa-producing Enzymes (Acpes) and Histone Acetylationsupporting
confidence: 61%
“…Nevertheless, following the four steps elaborated above for PCB, we found that a fraction of the CS enzyme also localizes to the nucleus (Figures 4D–4F) in a pyruvate-dependent manner (Figures 4F–4F″). While nuclear localization of PDH has been reported in other systems (Chueh et al, 2011; Sutendra et al, 2014), nuclear localization of a TCA cycle enzyme such as citrate synthase is an unexpected finding and led us to investigate the 2-cell embryo localization status of all TCA cycle enzyme isoforms that normally function in the mitochondrion. Beyond CS, the next TCA cycle step uses the mitochondrial enzyme aconitase 2 (ACO2) to metabolize citrate to iso-citrate.…”
Section: Resultsmentioning
confidence: 98%
“…Published literature provides precedence for extra-mitochondrial localization of PDH (Chueh et al, 2011; Mitra et al, 2005; Sutendra et al, 2014). Similar to our results in the pre-implantation embryo, all three subunits of PDH can be detected during the S phase of the cell cycle in the nucleus of lung cancer cell lines (Sutendra et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, GRIM19 largely inhibits STAT3 transcription by disrupting STAT3-DNA binding activity and further inhibits STAT3-mediated cell proliferation50. Pyruvate dehydrogenase complex-E2 (PDC-E2) has previously been reported to interact with STAT family members in a cytokine stimulation-dependent manner52. CBP-acetylated STAT3 translocates into mitochondria where STAT3 associates with PDC E1 and promotes pyruvate oxidation.…”
Section: Discussionmentioning
confidence: 99%